IMMERSIVE HISTORICAL LEARNING: USING VIRTUAL REALITY (VR) TO EXPLORE THE BOROBUDUR TEMPLE IN A HYBRID HISTORY CURRICULUM - Timi Ren; Malia Napit; James Wodrock (Yayasan Adra Karima Hubbi, 2025)
The integration of Virtual Reality (VR) into hybrid history education offers an innovative approach to enhance students’ engagement and understanding of cultural heritage. Traditional classroom instruction often struggles to provide immersive experiences that help learners grasp the spatial, artistic, and spiritual complexity of historical sites like Borobudur Temple. This study explores the implementation of VR as a pedagogical tool to promote experiential learning within a hybrid history curriculum that combines face-to-face and digital modalities. The research aims to examine how immersive VR experiences influence students’ motivation, historical empathy, and conceptual comprehension of Indonesian cultural heritage. A mixed-methods design was employed, involving 80 high school students divided into experimental (VR-assisted) and control (traditional hybrid) groups. Quantitative data were collected through pre- and post-tests measuring historical understanding and engagement, while qualitative data were obtained through student interviews and observation. The analysis used paired-sample t-tests and thematic coding to evaluate cognitive and affective outcomes. Results indicated that the VR-assisted group demonstrated significantly higher improvement in historical comprehension (p < 0.05) and engagement levels. Students reported that virtual exploration of Borobudur allowed them to visualize historical narratives and develop deeper cultural awareness through sensory immersion. The study concludes that integrating VR into hybrid history instruction fosters active, affective, and contextualized learning. The findings underscore the pedagogical value of immersive technology in revitalizing heritage education and promoting digital-humanistic approaches to cultural learning.